Multiconsensus of Second-Order Multiagent Systems with Input Delays. (17th February 2014) - Chen, Jie; Chi, Ming; Guan, Zhi-Hong; Liao, Rui-Quan; Zhang, Ding-Xue
Abstract : The multiconsensus problem of double-integrator dynamic multiagent systems has been investigated. Firstly, the dynamic multiconsensus, the static multiconsensus, and the periodic multiconsensus are considered as three cases of multiconsensus, respectively, in which the final multiconsensus convergence states are established by using matrix analysis. Secondly, as for the multiagent system with input delays, the maximal allowable upper bound of the delays is obtained by employing Hopf bifurcation of delayed networks theory. Finally, simulation results are presented to verify the theoretical analysis.